A general equilibrium impact study of the Emissions Reduction Fund in Australia by using a national environmental and economic model. (10th April 2019) - Nong, Duy
Abstract: Several climate change policies, such as emissions trading schemes and carbon taxes, have been implemented in many countries and regions around the world. However, the current Coalition Government in Australia does not prefer such methods and has argued that these policies would substantially increase the electricity price, and weaken the Australian competitiveness and the whole economy. Subsequently, the Government replaced the carbon tax policy in July 2014 with its Emissions Reduction Fund, which fundamentally uses the government budget of A$2.55 billion to buy emission abatements from polluters. There are major arguments among the Australian public about the efficiency and the effects of this approach, but the economic effects are still unidentified. This study aims to examine the economy-wide effects of this policy on the Australian economy by employing a national environmental and economic general equilibrium model so that Australians and international audience would be aware of the impacts and how the reverse auction and carbon subsidy work as a policy to reduce emissions at large scales across all sectors in a country. Results show that Australia only experiences relatively small impact on its economy. Real GDP only declines by 0.3%–0.4% over all scenarios. Industrial and private sectors also experience relatively small unfavourable impacts, but the output and export level of the agricultural commodity will decline substantially. The renewable sectors are expanded to compensate output reductions in fossil fuel electricity generation sectors, though the expansion is insufficient to compensate for the losses. Highlights: This study examines the impacts of the Emissions Reduction Fund in Australia. A detailed electricity computable general equilibrium model is developed. Abatement sectors are assumed to use the funding for improving efficiency. The Australia only experiences a mild contraction in the economy. Renewable electricity sectors are expanded but at relatively small rates.